Distributed Clustering Based Data Aggregation Algorithm for Grid Based WSN - Kaur, Amandeep; Gujral, Rajneesh Kumar (International Journal of Computer Sciences and Engineering, 2025)
Dynamic clustering in wireless sensor networks causes asymmetric division of cluster heads and extremely variable number of nodes in the clusters. Also, some of the clusters are spread over large areas in the network, causing limited spatial correlation between sensor nodes. These irregularities in cluster position have negative impact on the efficiency of a wireless sensor network. One critical issue in wireless sensor networks is how to collect sensed data in an energy-efficient way as the energy is a rare resource in a sensor node. Grid-Cluster-based aggregation is an effective architecture for data-gathering in wireless sensor networks. In this paper, we have developed a Distributed Clustering Based Data Aggregation (DCDA) algorithm for grid based WSN. In DCDA, cluster formation mechanism is based on a virtual-grid system. Simulation results show that DCDA improves the distribution of cluster heads and reduces the energy consumption within a range of 15%to 30% as compared to the existing protocols.